Proton pump inhibitors, genetic polymorphisms and response to clopidogrel therapy - Fernando, Himawan; Dart, Anthony M.; Peter, Karlheinz; Shaw, James A. (Thrombosis and Haemostasis, 2011)
Clopidogrel has become part of the mainstay of therapy for acute coronary syndromes and in patients post stenting. Clopidogrel is a pro drug and is metabolised by liver enzymes, particularly CYP2C19, into its active form. A considerable proportion of patients have a poor response to clopidogrel and this may be due to several factors. Genetic polymorphisms involved in clopidogrel’s absorption, metabolism and activity at the platelet may interfere with its antiplatelet actions. Further, proton pump inhibitors (PPI) may interfere with clopidogrel’s actions by functionally reducing the ability of CYP2C19 to convert clopidogrel to its active metabolite. By attenuating clopidogrel’s actions, both polymorphisms and drug interactions may increase the risk of thrombotic events during clopidogrel therapy. This review will explore the current evidence relating to the association between PPIs, genetic polymorphisms and poor response to clopidogrel. Routine genetic testing cannot be recommended for patients receiving dual antiplatelet therapy (DAPT). However, it may have a role for patients with an episode of stent thrombosis, prior to planned high-risk stenting or major bleeding. Regarding concomitant clopidogrel and PPI therapy, it is recommended that only patients with previous gastrointestinal (GI) bleeding or multiple risk factors for GI bleeding should be prescribed gastroprotection. This is due to the uncertainty surrounding the clinical significance of this interaction given the discordant biochemical and clinical data, conflicting results from observational studies and the limitations of the COGENT study. Pantoprazole seems least likely to interact with clopidogrel and most suitable for use in patients receiving DAPT.
Keywords: Clopidogrel; proton pump inhibitors; CYP2C19; genetic polymorphism; clopidogrel resistance